Switching to nilotinib versus imatinib dose escalation in patients with chronic myeloid leukaemia in chronic phase with suboptimal response to imatinib (LASOR): a randomised, open-label trial. Issue 12 (December 2016) - Cortes, Jorge E; De Souza, Carmino Antonio; Ayala, Manuel; Lopez, Jose Luis; Bullorsky, Eduardo; Shah, Sandip; Huang, Xiaojun; Babu, K Govind; Abdulkadyrov, Kudrat; de Oliveira, José Salvador Rodrigues; Shen, Zhi-Xiang; Sacha, Tomasz; et al.
Summary: Background: Optimal management of patients with chronic myeloid leukaemia in chronic phase with suboptimal cytogenetic response remains undetermined. This study aimed to investigate the safety and efficacy of switching to nilotinib vs imatinib dose escalation for patients with suboptimal cytogenetic response on imatinib. Methods: We did a phase 3, open-label, randomised trial in patients with chronic myeloid leukaemia in chronic phase with suboptimal cytogenetic response to imatinib according to the 2009 European LeukemiaNet criteria, in Latin America, Europe, and Asia (59 hospitals and care centres in 12 countries). Eligible patients were aged 18 years or older with Philadelphia chromosome-positive chronic myeloid leukaemia in chronic phase and Eastern Cooperative Oncology Group performance status of 0–2. Before enrolment, all patients had received 3–18 months of imatinib 400 mg once daily and had a suboptimal cytogenetic response according to 2009 ELN recommendations, established through bone marrow cytogenetics. By use of an interactive response technology using fixed blocks, we randomly assigned patients (1:1) to switch to nilotinib 400 mg twice per day or an escalation of imatinib dose to 600 mg once per day (block size of 4). Investigators and participants were not blinded to study treatment. Crossover was allowed for loss of response or intolerance at any time, or for patients with no complete cytogenetic response at 6 months. The primary endpoint was complete cytogenetic response at 6 months in the intention-to-treat population. Efficacy endpoints were based on the intention-to-treat population, with all patients assessed according to the treatment group to which they were randomised (regardless of crossover); the effect of crossover was assessed in post-hoc analyses, in which responses achieved after crossover were excluded. We present the final results at 24 months' follow-up. This study is registered withClinicalTrials.gov (NCT00802841 ). Findings: Between July 7, 2009, and Aug 29, 2012, we enrolled 191 patients. 96 patients were randomly assigned to nilotinib and 95 patients were randomly assigned to imatinib. Complete cytogenetic response at 6 months was achieved by 48 of 96 patients in the nilotinib group (50%, 95·18% CI 40–61) and 40 of 95 in the imatinib group (42%, 32–53%; difference 7·9% in favour of nilotinib; 95% CI −6·2 to 22·0, p=0·31). Excluding responses achieved after crossover, 48 (50%) of 96 patients in the nilotinib group and 34 (36%) of 95 patients in the imatinib group achieved complete cytogenic response at 6 months (nominal p=0·058). Grade 3–4 non-haematological adverse events occurring in more than one patient were headache (nilotinib group, n=2 [2%, including 1 after crossover to imatinib]; imatinib group, n=1 [1%]), blast cell crisis (nilotinib group, n=1 [1%]; imatinib group, n=1 [1%]), and QT prolongation (nilotinib group, n=1 [1%]; imatinib group, n=1 [1%, after crossover to nilotinib]). Serious adverse events on assigned treatment were reported in 11 (11%) of 96 patients in the nilotinib group and nine (10%) of 93 patients in the imatinib group. Seven (7%) of 96 patients died in the nilotinib group and five (5%) of 93 patients died in the imatinib group; no deaths were treatment-related. Interpretation: While longer-term analyses are needed to establish whether the clinical benefits observed with switching to nilotinib are associated with improved long-term survival outcomes, our results suggest that patients with suboptimal cytogenetic response are more likely to achieve improved cytogenetic and molecular responses with switching to nilotinib than with imatinib dose escalation, although the difference was not statistically significant when responses achieved after crossover were included. Funding: Novartis Pharmaceuticals.